Anatomía e impregnación con hidróxido de calcio y cipermetrina de la madera de tenaza Pithecellobium pallens (Tenaza) procedente de Tamaulipas, México - Hernández Vicente, Adriel (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
In the community of J. Agustin Castro also known Guayalejo their main source of work is the production of wooden furniture (Pithecellobium pallens) from its volunteers. The Tree of regrowth grows in parts of San Luis Potosi, Nuevo Leon, Coahuila and Tamaulipas predominantly. When the furniture has already been processed may have damage to the wood by wood-eating insects. This requires finding a substance that is accessible and affordable for artisans of the region, but is toxic to the organisms that cause damage to the wood, thereby reducing the attack caused by these insects and increasing sales for artisans the region of the municipality of Llera and around. The substance that can use in the population is the Cipermetrina, because is recommended like a product that can combat various plagues like cockroaches, flies, mosquitos, fleas, bed bug, scorpions, and dry wood termites. This substance have low level of toxicity for humans and domestic animals, but is highly dangerous for bees and the aquatic organisms, however this substance requires careful handling for their preparation, like the use of gloves, goggles, anti-gas mask and clothes for the protection for the workers. This product is used in the combat of agricultural pests and is derived from natural chemical products like the pyrethrins, this product are called pyretroids. Comparing methods for preservation without pressure. The absorption and retention showed a better result for the method of cold hot bath in the process desflemado. Cypermethrin by the method of desflemado causes irritation to the skin and eyes due to the warming that is submitted.

En la comunidad de J. Agustín Castro también conocido como Guayalejo, su principal fuente de trabajo es la elaboración de muebles de madera de tenaza (Pithecellobium pallens) a partir de sus rebrotes. El árbol de tenaza, crece en algunas regiones de San Luis Potosí, Nuevo León, Coahuila y predominantemente en Tamaulipas. Cuando los muebles ya han sido elaborados pueden presentar daño a la madera por insectos xilófagos. Para esto es necesario encontrar una sustancia que sea accesible y económica para los artesanos de la región, pero que sea tóxica para los organismos que causan daño a la madera, reduciendo con ello el ataque ocasionado por estos insectos e incrementando las ventas para los artesanos de la región del municipio de Llera y sus alrededores. Las sustancias que se pueden utilizar en la población son el Hidróxido de Calcio y las Cipermetrinas Estas sustancias tienen bajo nivel de toxicidad para los seres humanos y los animales domésticos, pero pueden afectar a los insectos que dañan a la madera. Los métodos para la preservación de la madera de tenaza que se utilizaron fueron los de desflemado, baño caliente-frío y de presión-vacío. Al comparar los métodos por preservación sin presión. La absorción y la retención mostraron un mejor resultado para el método de baño caliente frío que en el proceso por desflemado. La cipermetrina por el método de desflemado, produce irritación en la piel y los ojos debido al calentamiento al que es sometida.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2015-0654; Anatomía; Impregnación; Cipermetrina; Madera; Pithecellobium pallens; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/205